Fracture susceptibility of worn teeth - Keown, A.; Bush, M.; Ford, Chris; Lee, J.; Constantino, P.; Lawn, B. (Elsevier, 2012)
An experimental simulation study is made to determine the effects of occlusal wear on the capacity of teeth to resist fracture. Tests are carried out on model dome structures, using glass shells to represent enamel and epoxy filler to represent dentin. The top of the domes are ground and polished to produce flat surfaces of prescribed depths relative to shell thickness. The worn surfaces are then loaded axially with a hard sphere, or a hard or soft flat indenter, to represent extremes of food contacts. The loads required to drive longitudinal cracks around the side walls of the enamel to failure are measured as a function of relative wear depth. It is shown that increased wear can inhibit or enhance load-bearing capacity, depending on the nature of the contact. The results are discussed in the context of biological evolutionary pressures.